Manga: Invisible Cultural 'Imperialism' Through Popular Medium - Hafiz Aziz Ahmad; Alvanov Zpalanzani Mansoor (Wimba : Jurnal Komunikasi Visual, 2009)
The medium of comics is mostly known as popular culture medium, kidsâ stuff with their spandex superheroes, often sneered and looked down. However, through its long history, comics had proven to be contagious and influential medium toward the society, but unfortunately in the negative side. In United States of America (USA), the anti-comics movement led by Dr. Frederick Wertham accused that comics had bad and dangerous influence towards its young readers. This movement had brought comic in becoming public enemy number one in the past. Although people seem to see only the negative impact of this medium, on the contrary there is also the positive side. The power within comic is enormous, but unlike the tsunamilike power that could devastate anything on its path, comicâs power is unlikely otherwise: powerful yet penetrate in silent even to other culture and society as shown through the expansive âexportâ of Japanese comics, known as manga. Manga nowadays is known in most part of the world, especially in the South East Asia region. Imported as entertainment medium, manga influence could easily be seen in these countries, especially in Indonesia. Not only it proved to be booming in sales in these âforeignâ countries, manga also succeeded in penetrating to their culture, by creating devoted readers turn artists with manga-esque style and storytelling. The majority of young people in Indonesia now draw in this popular manga-esque style, following their favorite manga artists. Furthermore, it also changed how these people ways of reading: from left to right becoming right to left, creating the pretty boys genre in another medium and in the society itself. Unlike other popular culture medium (such as television) that its influence is clearly shown and catch the attention of people who rise against it, comic had proved otherwise. This paper is intended to observe how this phenomenon happened through qualitative analysis of comic culture (especially manga), the content within manga and its powerful and cultural influence with a case study of Indonesia.